USE OF INNOVATIVE METHODS IN TEACHING FOREIGN LANGUAGES - Fazliddinova Shaxzoda Xasanovna; Ochilova Noila Farmonovna (Journal of new century innovations, 2023)
In this article substantiates the idea that learning grammar is not only plays a crucial role in the study of a foreign language, but is practically equal to him